"To be lonely in your own loneliness": The interplay between self‐perceived loneliness and rheumatoid arthritis in everyday life: A qualitative study. (3rd June 2020) - Bay, Laila Twisttmann; Ellingsen, Torkell; Giraldi, Annamaria; Graugaard, Christian; Nielsen, Dorthe S.
Abstract: Objective: Loneliness has a negative impact on physical health, and rheumatoid arthritis symptoms can lead to social isolation. However, there is a lack of research exploring patients' perspectives on self‐perceived loneliness in everyday life with rheumatoid arthritis. The purpose of this study was to gain insight into the meaning and importance of self‐perceived loneliness among adult patients diagnosed with rheumatoid arthritis. Methods: This study was designed as a qualitative, exploratory interview study using a narrative framework. Semi‐structured interviews were conducted with Danish adults with rheumatoid arthritis. All interviews were recorded, transcribed verbatim, and analyzed within a narrative thematic framework. Results: Ten women and seven men were interviewed, aged between 18 and 73 years and a disease duration between 6 months and 40 years. Three themes were identified during the analysis: (1) explanations of loneliness in everyday life with rheumatoid arthritis, (2) disclosing or disguising loneliness, and (3) feelings of loneliness in social life. Conclusion: The findings from this study show that loneliness can be burdensome when living with RA. Narratives of loneliness can be hard for patients to disclose, so health care practitioners should take responsibility for legitimizing this subject. A narrative approach in consultations may be helpful to support patients and to encourage a dialogue about loneliness in everyday life with rheumatoid arthritis.